Modulation of Arabidopsis root growth by specialized triterpenes - Bai, Yuechen; Fernández-Calvo, Patricia; Ritter, Andrés; Huang, Ancheng C.; Morales-Herrera, Stefania; Bicalho, Keylla U. [UNESP]; Karady, Michal; Pauwels, Laurens; Buyst, Dieter; Njo, Maria; Ljung, Karen; Martins, José C.; et al. (Wiley, 2021)
Plant roots are specialized belowground organs that spatiotemporally shape their development in function of varying soil conditions. This root plasticity relies on intricate molecular networks driven by phytohormones, such as auxin and jasmonate (JA). Loss-of-function of the NOVEL INTERACTOR OF JAZ (NINJA), a core component of the JA signaling pathway, leads to enhanced triterpene biosynthesis, in particular of the thalianol gene cluster, in Arabidopsis thaliana roots. We have investigated the biological role of thalianol and its derivatives by focusing on Thalianol Synthase (THAS) and Thalianol Acyltransferase 2 (THAA2), two thalianol cluster genes that are upregulated in the roots of ninja mutant plants. THAS and THAA2 activity was investigated in yeast, and metabolite and phenotype profiling of thas and thaa2 loss-of-function plants was carried out. THAA2 was shown to be responsible for the acetylation of thalianol and its derivatives, both in yeast and in planta. In addition, THAS and THAA2 activity was shown to modulate root development. Our results indicate that the thalianol pathway is not only controlled by phytohormonal cues, but also may modulate phytohormonal action itself, thereby affecting root development and interaction with the environment.
Keywords: Arabidopsis thaliana; auxin; brassinosteroid; jasmonate; NINJA; thalianol; thalianol acyltransferase 2 (THAA2); thalianol synthase (THAS)